Chemical constituents and free radical scavenging activity of corn pollen collected from Apis mellifera hives compared to floral corn pollen at Nan, Thailand - Chantarudee, Atip (BioMed Central, 2012)
BACKGROUND: Bee pollen is composed of floral pollen mixed with nectar and bee secretion that is collected by foraging honey (Apis sp.) and stingless bees. It is rich in nutrients, such as sugars, proteins, lipids, vitamins and flavonoids, and has been ascribed antiproliferative, anti-allergenic, anti-angiogenic and free radical scavenging activities. This research aimed at a preliminary investigation of the chemical constituents and free radical scavenging activity in A. mellifera bee pollen. METHODS: Bee pollen was directly collected from A. mellifera colonies in Nan province, Thailand, in June, 2010, whilst floral corn (Zea mays L.) pollen was collected from the nearby corn fields. The pollen was then sequentially extracted with methanol, dichloromethane (DCM) and hexane, and each crude extract was tested for free radical scavenging activity using the DPPH assay, evaluating the percentage scavenging activity and the effective concentration at 50% (EC(50)). The most active crude fraction from the bee pollen was then further enriched for bioactive components by silica gel 60 quick and adsorption or Sephadex LH-20 size exclusion chromatography. The purity of all fractions in each step was observed by thin layer chromatography and the bioactivity assessed by the DPPH assay. The chemical structures of the most active fractions were analyzed by nuclear magnetic resonance. RESULTS: The crude DCM extract of both the bee corn pollen and floral corn pollen provided the highest active free radical scavenging activity of the three solvent extracts, but it was significantly (over 28-fold) higher in the bee corn pollen (EC(50) = 7.42 ± 0.12 μg/ml), than the floral corn pollen (EC(50) = 212 ± 13.6% μg/ml). After fractionation to homogeneity, the phenolic hydroquinone and the flavone 7-O-R-apigenin were found as the minor and major bioactive compounds, respectively. Bee corn pollen contained a reasonably diverse array of nutritional components, including biotin (56.7 μg/100 g), invert sugar (19.9 g/100 g), vitamin A and β carotene (1.53 mg/100 g). CONCLUSIONS: Bee pollen derived from corn (Z. mays), a non-toxic or edible plant, provided a better free radical scavenging activity than floral corn pollen.